Case Report: Anomalous Origin of the Right Coronary Artery From the Left Sinus of Valsalva With Aortic Dissection: New Myocardial Ischemia Mechanism - Xie, Zhongshang; Zou, Junlin; Zhu, Hong; Bu, Haisong (Frontiers in Cardiovascular Medicine, 2022)
The aortic anomaly of the right coronary artery (AAORCA) originating from the left aortic sinus (LCS) is a rare malformation that may result in sudden cardiac death (SCD), which may be due to the dilated aorta-pulmonary artery affecting the blood supply of the coronary artery. However, there are still some disputes about the treatment of the AAORCA. Herein, we present a rare case of AAORCA from the LCS with aortic dissection (AD). Considering the risk of dissection rupture and SCD, an emergency surgery of aortic replacement and coronary anomaly correction was performed successfully for the patient. This report illustrated that AAORCA complicated with acute AD (AAD) is lethal and may promote the occurrence of coronary ischemia or sudden death by a new “double-kill” mechanism that myocardial ischemia was based on the extent of a fixed and a dynamic component like slit-like ostium, proximal narrowing, acute take-off angle and intramural course with the elliptic vessel shape. There is no doubt that surgery is the best treatment option for the AAORCA with AAD.